Humanitarian Operations and the UN Sustainable Development Goals - Maria Besiou; Alfonso J. Pedraza-Martinez; Luk N. Van Wassenhove (Production and Operations Management, 2021)
During emergencies humanitarian supply chains need to respond swiftly, very often without time for good planning that may end up in excessive waste and emissions. This short-term focus on saving people's lives during disaster responses may harm communities and the planet in the long-run. Even long-term (development) focus on improving the life conditions of the poor may be either unsustainable due to the lack of community involvement or inequitable due to lack of resources. At the same time, countries closer to fulfilling the United Nations sustainable development goals (SDGs) suffer less from disasters but still struggle with issues such as social equity. There appears to be an important link between humanitarian operations and SDGs. This special issue focuses on this interaction through a rich variety of contributions using different methodologies, data and lenses, while proposing ways to advance the SDGs. The special issue clearly shows the value operations management can bring to short-term and long-term problems society faces.
Keywords: 650; humanitarian operations; United Nations sustainable development goals; humanitarian logistics; disaster management cycle; sustainability